The genus Sphecodes Latreille 1804 (Hymenoptera: Apoidea: Halictidae) in Central Asia - Astafurova, Yulia V.; Proshchalykin, Maxim Yu. (Zootaxa, 2017)
Available information on the bees of the genus Sphecodes Latreille 1804 in Central Asia is summarized. Twenty-eight species are currently known from this area. Sphecodes turanicus Astafurova & Proshchalykin, sp. nov. is described from Uzbekistan, Turkmenistan, Tajikistan, and Kazakhstan. Eight species: Sphecodes anatolicus Warncke 1992, S. crassus Thomson 1870, S. croaticus Meyer 1922, S. ferruginatus Hagens 1882, S. miniatus Hagens 1882, S. pellucidus Smith 1845, S. rufiventris (Panzer 1798), and S. spinulosus Hagens 1875 are newly recorded from Central Asia. The status of S. nurekensis Warncke 1992, stat. nov. is raised to species level; S. tadschicus Blüthgen 1935, stat. resurr. is reinstated as a valid taxon. A lectotype is designated for S. gracilior Morawitz 1893. Illustrated keys to both males and females of all species known from Central Asia are provided.